(untitled) (Eurasian Journal of Religious Studies, 2022)
Kazakhstan has set itself a new direction of development, after gaining independence, due to the need to find its place on the stage of global political competition with the appropriate level of resistance. New domestic strategies, goals and objectives have been born: to join the ranks of advanced developed countries, to present itself to the world as a democratic state governed by the rule of law, to form a spiritually mature society, to form competitive individuals in the information society, to improve the welfare of the country, etc. For now, this, in fact, requires a different approach to the vital requirements and conditions of human capital of the country. The ultimate destination here is the consideration of each person in the country as a human capital. It is quite natural that human capital, particularly in the spiritual spheare has its own conditions and principles, norms and life orientations. Respectively, the main value in today’s society is information, which is now becoming a tool that directly affects the development of society, without barricading the border between states. No wonder that many scientists have proved in many areas that the consciousness of the population consuming foreign information, ie media products, varies from period to period. And what is the response of the traditional Sunni-Hanafi Islam, with which most of the country associates itself, to respond to the influence of modern information? Do spiritual values are one of the main factors of human capital stability to play their role at the required level? To meet the answers to this question and other additive questions, a sociological study have been conducted among the clergy in religious institutions of the country – mosques. Based on answers that have been obtained, the proposed article is attempted to reveal the results of the analysis of empirical data. Keywords: information society, human capital, spiritual capital, religion, religious values